Application of non-contrasted computed tomography and diffusion-weighted imaging protocols for endovascular treatment selection in patients with late-presenting or wake-up strokes - Ming, Wei; Shuyuan, Wang; Hecheng, Ren; Lin, Ma; Long, Yin (Arquivos de Neuro-Psiquiatria, 2021)
Background: Among patients with acute ischemic stroke with a mismatch between deficit severity and infarct volume, thrombectomy performed within a 6-24 hours time window has efficacy and safety similar to treatment within 6 hours. However, whether magnetic resonance imaging with T2 diffusion-weighted imaging (DWI) is feasible remains to be validated. Objective: To investigate prognosis among stroke patients receiving endovascular treatment (EVT) within 6 hours and 6-24 hours using non-contrasted computed tomography (NCCT) and DWI. Methods: Overall, 209 anterior-circulation ischemic stroke patients with large-vessel occlusion who underwent EVT were divided into ≤ 6 hours and 6-24 hours groups. Patients presenting symptoms within 6 hours were treated if their NIHSS score was ≥ 7 and ASPECTS score was ≥ 5, whereas those with wake-up stroke (WUS) or presenting symptoms 6-24 hours after last seen well (WUS/late-presenting stroke, LPS) were managed if their NIHSS score was ≥ 7 and ASPECTS score was ≥ 5. Results: The percentages of patients undergoing intracranial stenting and intracranial ballooning without stenting significantly differed between two groups (p < 0.001). Grades 0, 1, 2a and 2b recanalization rates did not differ between the 6 hours and 6-24 hours groups (all p > 0.05). Grade 3 recanalization rate in the 6 hours group was significantly lower than in the 6-24 hours group (p = 0.043). The 3-month Rankin Scale score did not significantly differ between the two groups (p = 0.629). Conclusions: EVT is a safe and effective treatment for patients with WUS and LPS selected through NCCT and DWI-based simple imaging.
Keywords: Endovascular Treatment; Non-contrast Computed Tomography; Diffusion Magnetic Resonance Imaging; Stroke